Exploration of Arithmetic Concepts in Jetis Batik at Namiroh Batik Shop, Sidoarjo, East Java - Novalita Machmara; Nuril Huda Mohammad; Fransiska Safenia Kayo; Ruben Tildjuir; Sulis Janu Hartati (Prodi Tadris Matematika Fakultas Tadris Umum, 2026)
This research aims to explore arithmetic concepts in the process of making Jetis Sidoarjo Batik at the Namiroh Batik Shop, as mathematics is often embedded in cultural production practices but not explicitly recognized in formal learning contexts. This study employs a qualitative method with an ethnographic design. The data collection techniques in this study include observation, interviews, and documentation. The data analysis techniques used include data reduction, data display, and conclusion drawing. The validity of the data is strengthened through source triangulation. The results of the study show that there are arithmetic concepts in the production activities of Jetis Batik, including measurement and calculation operations in determining the size of the fabric, comparison and fractions in the dye mixing process, time calculation and unit conversion in the production stage, and social arithmetic in determining the selling price. These findings indicate that arithmetic functions as a practical and contextual tool in real-life cultural activities. Therefore, Jetis Batik production can be utilized as a meaningful context for mathematics learning in elementary schools, particularly in teaching measurement, fractions and ratios, time conversion, simple averages, and profit–loss concepts.